Parallel trials and social condemnations as functional equivalents to punishment: arguments in favor of a sentence reduction due to certain social reactions - Bide, Jerónimo (2024)
In this article will be defended the thesis that parallel trials and social condemnations can often serve as functional equivalents to forensic punishment –most of the times, only partially– and, insofar as they justify a reduction in the formal sentence, should be considered during the judicial sentencing process.To support this argument, which is considered correct if the proportionality of penalties is to be consistently respected, the author will begin with the theory of norms, focusing particularly on the sanction norm; then introduce the theory of functional equivalents to punishment, considering both its factual and expressive dimensions; and finally, analyze how both retributive and preventive aspects, along with considerations of desert and necessity, influence the determination of punishment.